Optimizing Gram-Negative Bacteria Isolation from Children Diarrheal Stool Samples in Jakarta: A Comparative Analysis of Six Culture Media - Abdelrazig, Omnia Amir Osman; Fadilah, Fadilah; Prasetyo, Dimas Seto; Saharman, Yulia Rosa; Hegar, Badriul (Al-Hayat: Journal of Biology and Applied Biology, 2024)
The prevalence of diarrheal illnesses in Indonesia remains a significant concern among children under the age of five, evident through diagnostic findings and symptomatic manifestations, leading to increased rates of mortality and morbidity. This study aimed to identify, isolate, and culture gram-negative bacteria responsible for childhood diarrhea. Twenty stool samples were collected from children under the age of 5 with acute diarrhea in Jakarta health centres and hospitals between October 2023 to January 2024. These samples were inoculated onto selective agars to facilitate the growth of gram-negative bacteria. After a 24-hour incubation period, colonies suspected to be E. coli, K. pneumoniae, Salmonella, Shigella, or Vibrio were identified using the Vitek-2 compact system. The results revealed a notable presence of Gram-negative bacteria in all the fecal samples from diarrheal children, with Escherichia coli (E. Coli) and Klebsiella pneumoniae (Klebsiella p) as the predominant species. In conclusion, our study, utilizing various cultures and the Vitek-2 compact system, elucidates the microbial landscape driving diarrheal morbidity in Indonesian children under five, with E. Coli and klebsiella pneumoniae emerging as prevalent contributors to childhood diarrhea in this population.